Which method is more suitable for nocardia isolation of polymicrobial site? - Bafghi, Mehdi Fatahi; Nasab, Masoumeh Rasouli; Habibnia, Shahi (Bangladesh Journal of Medical Microbiology, 2013)
No abstract DOI: http://dx.doi.org/10.3329/bjmm.v7i2.19374 Bangladesh J Med Microbiol 2013; 07(02): 1